The Contemporary Serbian-Slovak Literary Dialogue - Valent Belić, Zdenka (Napredak, 2026)
The Serbian-Slovak relations form a longstanding bridge between the two Slavic nations. The roots of these relations go as far back as the 19th century and were originally inspired by national revival and col lective effort to gain national independence. Literary translations stand for a significant aspect of cultural ties, while extensive translation activities make sure that there is both deep understanding and cultural dialogue. The role of translators is important for the purpose of preserving this form of familiarity. There has recently been an increase in the number of translated works, which has been confirmed by meticulously reviewing the Combined Catalogue of the National Bank of Serbia, the Matica Srpska Library, and the Slovak National Library. Thanks to a large number of translators and publishers, the Serbian-Slovak literary dialogue in recent decades has been on the substantial increase.
Keywords: Serbian-Slovak ties; literary translation; translators; Slovak literature; Serbian literature